Skating School: Pink Skate Party - Chapman, Linda (Penguin Group, 2010)
Welcome to a magical world where dreams come true . . . Emily loves dancing at ice-skating school and this week the girls get to invent their own routine - and design their costumes! Soon Emily is busy practising - but she is so eager to succeed that she forgets her friends. Will Emily remember that being a good friend means more than winning the pair of precious pink skates?
Keywords: Juvenile literature-Fiction